GlucoMedix®, an extract of Stevia rebaudiana and Uncaria tomentosa, reduces hyperglycemia, hyperlipidemia, and hypertension in rat models without toxicity: a treatment for metabolic syndrome - León F. Villegas Vílchez; Julio Hidalgo Ascencios; Thomas P. Dooley (BMC, 2022)
Abstract Background The objective of this in vivo study is to evaluate in five rat models the pharmacologic effects and toxicity of a commercial hydro-alcoholic extract, GlucoMedix®, derived from Stevia rebaudiana and the pentacyclic chemotype of Uncaria Tomentosa (Willd.) DC, for use as a treatment for metabolic syndrome. The extract contains phytochemicals of Stevia (e.g., steviol glycosides) and Uncaria (e.g., pentacyclic oxindole alkaloids, but lacks tetracyclic oxindole alkaloids). Methods The pharmacologic assessments in three rat models include reductions in chemically induced hyperglycemia, hyperlipidemia (cholesterol and triglycerides), and hypertension, all of which are comorbidities of metabolic syndrome. Acute toxicity and 28-day subacute toxicity were assessed in rat models at doses higher than those used in the efficacy models. Results The acute oral toxicity was evaluated in Holtzman rats and the extract did not produce acute toxic effects or lethality, with the LD50 > 5000 mg/kg (extract wet weight). Furthermore, subacute oral toxicity was evaluated in rats for 28 days at daily doses as high as 2000 mg/kg without toxicity or abnormal clinical chemistry or hematological effects. Daily oral doses of 250 - 1000 mg/kg were used to evaluate the treatment effects in hyperglycemic (alloxan-induced and glibenclamide-controlled), hyperlipidemic (cholesterol-induced and atorvastatin-controlled), and hypertensive (L-NAME-induced and enalapril-controlled) rat models. Alloxan-induced hyperglycemia was reduced in a dose-dependent manner within 28 days or less. Cholesterol-induced hyperlipidemic rats exhibited dose-dependent reductions in cholesterol and triglycerides at 21 days. Furthermore, GlucoMedix® produced a dose-dependent decrease in systolic and diastolic arterial blood pressure in L-NAME-induced hypertensive rats at 28 days. Conclusions The five in vivo rat models revealed that the all-natural phytotherapy GlucoMedix® is a safe and effective treatment for hyperglycemia, hyperlipidemia, and hypertension. This extract is expected to affect multiple comorbidities of metabolic syndrome, without any acute or subacute oral toxicity in humans. Although multiple prescription drugs are well known for the treatment of individual comorbidities of metabolic syndrome, no drug monotherapy concurrently treats all three comorbidities.